Characterisation of responses to PGE2-G in the porcine coronary artery, rat aorta and murine microglial cell line BV-2 - Vadgama, Anisha (2019)
Prostaglandin glyceryl esters are derived from cyclooxygenase-2 oxygenation of the endocannabinoid 2-arachidonoylglycerol. Prostaglandin E2 glyceryl ester (PGE2G) may be involved in inflammation but very little else is known about its patho/physiological roles. A recent study identified interaction of PGE2G with P2Y6 receptors in isolated cells. P2Y6 receptors are involved in cardiovascular regulation and UDP is the agonist. In this study, it was investigated whether PGE2G can influence vascular contractility through P2Y6 receptors.